Biomechanical properties of polymer-infiltrated ceramic crowns on one-piece zirconia implants after long-term chewing simulation - Pia Baumgart; Holger Kirsten; Rainer Haak; Constanze Olms (SpringerOpen, 2018)
Abstract Background Implant and superstructure provide a complex system, which has to withstand oral conditions. Concerning the brittleness of many ceramics, fractures are a greatly feared issue. Therefore, polymer-infiltrated ceramic networks (PICNs) were developed. Because of its high elastic modulus, the PICN crown on a one-piece zirconia implant might absorb forces to prevent the system from fracturing in order to sustain oral forces. Recommendations for the material of superstructure on zirconia implants are lacking, and only one study investigates PICN crowns on these types of implants. Accordingly, this study aimed to examine PICN crowns on one-piece zirconia implants regarding bond strength and surface wear after long-term chewing simulation (CS). Methods Twenty-five hybrid ceramic crowns (Vita Enamic, Vita Zahnfabrik) were produced using computer-aided design/computer-aided manufacturing (CAD/CAM) technology and adhesively bonded (RelyX™ Ultimate, 3M ESPE) to zirconia implants. Twenty of the specimens underwent simultaneous mechanical loading and thermocycling simulating a 5-year clinical situation (SD Mechatronik GmbH). Wear depth and wear volume, based on X-ray micro-computed tomography volume scans (Skyscan 1172-100-50, Bruker) before and after CS, were evaluated. All crowns were removed from the implants using a universal testing machine (Z010, Zwick GmbH&Co.KG). Subsequently, luting agent was light microscopically localized (Stemi 2000-C, Zeiss). With a scanning electron microscope (SEM, Phenom™ G2 pro, Phenom World), the area of abrasion was assessed. Results 1.After CS, none of the tested crowns were fractured or loosened.2.The maximum vertical wear after CS was M = 0.31 ± 0.04 mm (mean ± standard deviation), and the surface wear was M = 0.74 ± 0.23 mm3.3.The pull-off tests revealed a 1.8 times higher bond strength of the control group compared to the experimental group (t(23) = 8.69, p < 0.001).4.Luting agent was mostly located in the crowns, not on the implants.5.The area of abrasion showed avulsion and a rough surface. Conclusions PICN on one-piece zirconia implants showed high bond strength and high wear after CS.